Cross layer design for RFID systems - Hou, Yuxiao (2017)
Recently, Radio Frequency IDentification (RFID) systems are widely adopted in real world applications, such as inventory management, item tracking, and access control. Some fundamental RFID operations underlying almost every application, like identification, population estimation, missing tag detection should be executed with high efficiency and accuracy. Although a rich amount of works are devoted to improve the performances of these fundamental operations, most of these works suffer greatly from unconscious and frequent tag collisions -- especially in a large tag set -- and hence produce limited performance gains. In this thesis, I adopt a cross-layer design principle to facilitate these traditional MAC-layer operations with physical-layer information extracted from each colliding tag response signal, which is largely ignored by previous works. Specifically, two types of RFID operations are considered: population (or cardinality) estimation and identification.